Linguistic Complexity of Bali’s Tourism Actors: The Perspectives of Translanguaging and Language Ideologies - Tuntun Sinaga,; Saortua Marbun, (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
It is widely known that international tourist destinations, such as Bali, serve as sites where multiple languages co-exist. This linguistic diversity has shaped how local people (speakers) use language in their interactions. However, research on language, in Bali’s tourism context, has treated languages as separate entities. Therefore, this study explored Balinese tourism actors’ experiences and perspectives of their language practice in relation to language ideologies. This study is qualitative in nature, adopting semi-structured interviews with Balinese tourism actors for data collection. The collected data were analyzed using thematic analysis. This study identified two key findings: (1) translanguaging as an economic and cultural bridge; and (2) translanguaging as a sign of openness. The findings suggest that multilingualism serves as a resource for meaning making, which contradicts the monolingual perspective that sees languages as separate. This study concludes with implications and recommendations for future research.
Keywords: translanguaging; language ideologies; tourism and globalization; cultural identity; language practices; Bali